Map the Meal Gap: Exploring Food Insecurity at the Local Level. (24th July 2014) - Gundersen, Craig; Engelhard, Emily; Waxman, Elaine
Abstract : The burgeoning food insecurity literature in the United States has provided a portrait of the causes and consequences of food insecurity. One underexplored aspect is the spatial diversity in food insecurity across the United States. In response, Feeding America has been releasing annual county‐level food insecurity estimates since 2010. In this article, we describe the methods underlying these estimates, followed by answers to the following: What are the state‐level determinants of food insecurity? What is the distribution of food insecurity across counties in the United States? How do the county‐level food insecurity estimates generated in Map the Meal Gap compare with other sources?